The Influence Of Human Resource Development On Human And Organizational Culture On Employee Performance Wyndham Opi Hotel Palembang - Iraawan, Rikky; Naruliza, Esty; Mario, Asma (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study focuses on the analysis of the influence of organizational culture and human resource development on employee performance, both partially and simultaneously. The location of the study was at Wyndham Opi Hotel Palembang involving 78 employees as samples. Based on the results of the study, all statement items were declared valid because the calculated r value was greater than the r table of 0.1876. The research instrument was also proven reliable with a Cronbach's alpha value ≥ 0.6. The normality test showed that the data were normally distributed. The heteroscedasticity test through scatterplot indicated no symptoms of heteroscedasticity, marked by random distribution of points without a particular pattern. The multicollinearity test showed that no symptoms of multicollinearity were found because the VIF value of 4,250 was still below the threshold of 10. The F test (simultaneous) showed that the variables of human resource development and organizational culture together had a significant effect on employee performance, with a calculated F value of 98,142 greater than the F table of 2.37. The t-test (partial) also showed significant results, namely human resource development with a t count of 3.246 > 1.293 and a significance of 0.002 < 0.05, and organizational culture with a t count of 3.772 > 1.293 and a significance of 0.000 < 0.05. Human resource development contributed 32.5% to employee performance, while organizational culture contributed 39.9%. The coefficient of determination (R²) of 0.724 indicates that 72.4% of the variation in employee performance can be explained by these two variables, while the remaining 27.6% is influenced by other factors outside the model, such as leadership style and training.